INTRODUCTION OF RHINOCEROS SOFTWARE FOR EXERCISES OF SUBJECT GEOMETRIC SURFACES IN ARCHITECTURE - Sonja KRASIC; Zlata TOSIC; Petar PEJIC (Journal of Industrial Design and Engineering Graphics, 2019)
In contemporary architecture, free curved forms of objects, or parametrically modeled shapes, are in the expansion. The authors had an interest to upgrade student’s knowledge with complex geometry design and contemporary software such as Rhinoceros. In that manner we made an exercise templates, that our students on Architecture used in elected subject „Geometric Surfaces in Architecture“ where they learned about types, usage and design of geometric surfaces in architecture. By creating templates we reassure precise, faster and planed work with students as they obtain every possible explanation, for every exercise and homework that they have to master. Moreover this teaching method allows students not only to pass the course and learn new modeling and design techniques, but also keeping the prepared material as support for future architectural work.